Identification and activity of acetate-assimilating bacteria in diffuse fluids venting from two deep-sea hydrothermal systems. Issue 3 (8th December 2014) - Winkel, Matthias; Pjevac, Petra; Kleiner, Manuel; Littmann, Sten; Meyerdierks, Anke; Amann, Rudolf; Mußmann, Marc
Abstract: Diffuse hydrothermal fluids often contain organic compounds such as hydrocarbons, lipids, and organic acids. Microorganisms consuming these compounds at hydrothermal sites are so far only known from cultivation-dependent studies. To identify potential heterotrophs without prior cultivation, we combined microbial community analysis with short-term incubations using 13 C-labeled acetate at two distinct hydrothermal systems. We followed cell growth and assimilation of 13 C into single cells by nanoSIMS combined with fluorescence in situ hybridization (FISH). In 55 °C-fluids from the Menez Gwen hydrothermal system/Mid-Atlantic Ridge, a novel epsilonproteobacterial group accounted for nearly all assimilation of acetate, representing the first aerobic acetate-consuming member of the Nautiliales . In contrast, Gammaproteobacteria dominated the 13 C-acetate assimilation in incubations of 37 °C-fluids from the back-arc hydrothermal system in the Manus Basin/Papua New Guinea. Here, 16S rRNA gene sequences were mostly related to mesophilic Marinobacter, reflecting the high content of seawater in these fluids. The rapid growth of microorganisms upon acetate addition suggests that acetate consumers in diffuse fluids are copiotrophic opportunists, which quickly exploit their energy sources, whenever available under the spatially and temporally highly fluctuating conditions. Our data provide first insights into the heterotrophic microbial community, catalyzing an under-investigated part of microbial carbon cycling at hydrothermal vents. Abstract : This is the first cultivation-independent study using stable isotopic and molecular tools addressing the heterotrophic potential of free-living microbes in diffuse hydrothermal fluids. Abstract :